The Effect Of Organization Culture, Rewards, Job Satisfaction And Job Stress On Lecturer’s Performance At UIN Ar-Raniry anda Aceh - Iis Marsithah; Benyamin; Nasrun (Publisher Cv. Inara, 2021)
The purpose of this study was to find out and examine: (1) the lecturer’s performance model built on associative causal relationships between exogenous variables and endogenous variables, (2) the effect of organizational culture to job satisfaction, (3) the effect of rewards to job satisfaction, (4) the effect of organizational culture to job stress, (5) the effect of rewards to job stress,(6) the effect of organizational culture to lecturer’s performance, (7) the effect of rewards to lecturer’s performance, (8) the effect of job satisfaction to lecturers performance, and, (9) the effect of job stress to lecturers performance. The population is all lecturer as many as 486 people. The research sample of 219 people was determined by the Slovin formula. Data collection is done by using a questionnaire with five answer choices. The sampling technique were used proportional random sampling. The instruments were used first tried out to respondent outside the sample to obtain validity and reliability instruments. Validity test uses Product Moment correlation, while to test its reliability with Alpha formula from Cronbach. Before testing the hypothesis, especially before the test is calculated, the requirements of the analysis include: normality data test and regression linearity test.The results showed (1) Obtained the lecturer’s performance model UIN Ar-Raniry Banda Aceh, (2) there is positive direct effect of organizational culture to job satisfaction 1,9%, (3) there is positive direct effect of rewards to job satisfaction 1,9%, (4) there is negative direct effect of organizational culture to job stres11,2%, (5) there is negative direct effect of rewards to job stress 2%, (6) there is positive direct effect of organizational culture to lecturer’s performance 7,9% include indirect effect through job satisfaction 0,6% and job stress 1,8%, (7) there is positive direct effect of rewards to lecturer’s performance 2,8% include indirect effect through job satisfaction 0,4% and job stress 0,7%,(8) there is positive direct effect of job satisfaction to lecturer’s performance 1,5%, and (9) there is positive direct effect of job stress to lecturer’s performance 3%.Based on the acceptance of the research hypothesis, it is found a fixed model that describes the structure of causal relationships between organizational culture, rewards, job satisfaction, job stress and lecturer’s performance at UIN Ar-Raniry Banda Aceh. The organizational behavior has bigger influence than the other variable to lecturer’s performance. The next variable was job stress, rewards, and job satisfaction has lowest influence than the other variable to lecturer’s performance.